Transformation of Organizational Culture and Job Satisfaction in Building HR Capabilities at BPBA - M. Nur, Edwar; Saiful Bahri, T.; Fadhla, Teuku (Publisher Cv. Inara, 2025)
This study examines the impact of organizational culture and contributions on employee job satisfaction at the Aceh Disaster Management Agency (BPBA). Human Resource Development is critical for organizational success, especially in disaster management. Utilizing a sample of 100 BPBA employees, the study employed canonical correlation analysis to assess the relationship between organizational contributions, culture, and job satisfaction. Results indicate that organizational culture significantly influences job satisfaction (? = 0.327, p < 0.001), highlighting the importance of collaborative environments, open communication, and employee appreciation. Conversely, while important, organizational contributions showed no significant direct effect (? = 0.078, p = 0.358). The findings emphasize the role of a supportive organizational culture in fostering job satisfaction and employee motivation. The model accounts for 26.2% of the variability in job satisfaction, suggesting that additional factors also contribute. This research underscores the need for strategic improvements in organizational culture to enhance employee welfare and productivity.